2013
DOI: 10.1038/nmat3667
|View full text |Cite
|
Sign up to set email alerts
|

Carbon monoxide-induced adatom sintering in a Pd–Fe3O4 model catalyst

Abstract: The coarsening of catalytically active metal clusters is often accelerated by the presence of gases, but the role played by gas molecules is difficult to ascertain and varies from system to system. We use scanning tunnelling microscopy to follow the CO-induced coalescence of Pd adatoms supported on the Fe3O4(001) surface at room temperature, and find Pd-carbonyl species to be responsible for mobility in this system. Once these reach a critical density, clusters nucleate; subsequent coarsening occurs through cl… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

26
306
1
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 272 publications
(335 citation statements)
references
References 38 publications
(50 reference statements)
26
306
1
2
Order By: Relevance
“…Although they are also observed in the proximity of surface defects such as steps edges, this paper discusses bright protrusions other than those. Previous STM studies of a freshly prepared Fe 3 O 4 (001) surface have also observed them [5,8,21,27,28]. As a result of XPS measurements of the surface, we have observed no peaks derived from impurities such as CO and no peak shifts for O and Fe (data not shown).…”
Section: Resultssupporting
confidence: 69%
“…Although they are also observed in the proximity of surface defects such as steps edges, this paper discusses bright protrusions other than those. Previous STM studies of a freshly prepared Fe 3 O 4 (001) surface have also observed them [5,8,21,27,28]. As a result of XPS measurements of the surface, we have observed no peaks derived from impurities such as CO and no peak shifts for O and Fe (data not shown).…”
Section: Resultssupporting
confidence: 69%
“…27 Foreign metal atoms deposited onto this surface adsorb in an oxygen-bridging site in one specific location of the unit cell. 39,[41][42][43] The force-relaxed structure of a Co adatom (Co 2+ ) in such site is shown in Figure 6(a).…”
Section: B Dft Resultsmentioning
confidence: 99%
“…Among them, based on reported work 39,[41][42][43] and our DFT calculations, we have considered the adatom site on top of two surface oxygen cations in a bridge configuration, the surface octahedral positions, and the subsurface octahedral positions. The latter, as described in the Sec.…”
Section: Discussionmentioning
confidence: 99%
“…The published binding energy of 2.25 eV and charge state of +0.6 e -were calculated using the DBT structure [262], but these values do not change significantly for the SCV structure as the local environment around the adsorption site is similar. High coverages of Pd adatoms can be achieved, which suggests the Pd-Pd dimer is unstable with respect to two adatoms (as discussed for Ag, above).…”
Section: Palladiummentioning
confidence: 99%
“…High coverages of Pd adatoms can be achieved, which suggests the Pd-Pd dimer is unstable with respect to two adatoms (as discussed for Ag, above). However, in contrast to Au and Ag, the stability of the Pd 1 /Fe 3 O 4 (001) system is highly sensitive to CO [262]. Indeed, even in a pressure of 5×10 -10 mbar CO, Pd adatoms sinter completely to form Pd nanoparticles in under an hour (see Figure 84).…”
Section: Palladiummentioning
confidence: 99%